KEKUATAN HUKUM PREAMBULE UUD 1945 DALAM SISTIM HUKUM KETATANEGARAAN REPUBLIK INDONESIA (Studi Hermeneutika-Fenomenologi, Metastudi-Metateorisasi, Dan Perbandingan Sistim Hukum Tata Negara) - POLAMOLO, SUSANTO (Dinamika Hukum, 2015)
The purpose of this study is to examine and analyze the force of law Preamble 1945 in the Indonesian legal system of the State governance, both at the level of legal theory and praxis. Background problem from two issues, first, about the historicity Preamble that in many studies present with different explanations, particularly in relation to the history of the birth of Pancasila. Secondly, in the case where the theoretical Preamble scientifically unexplained laws, especially how the strength and position of legally binding and guiding rule of law under the 1945 Constitution. The method used them, from the point of nature is divided into three types, namely exploratory, descriptive, and explanatory. A multidisciplinary focus on a mix of several existing science, in this case as hermeneutic-phenomenology, meta study-meta theory, and comparative constitutional law system of the State. In addition, this study in relation to Preamble 1945 also examine and analyze legal doctrinal and non-doctrinal. While the shape of the corner, this research focuses on three things: first, to diagnose because the emergence of a problem begins from historicity, to the problem of theorising law, following the practice. Secondly, it aims to give an overview prescriptive fit the facts. Third, do a critical evaluation. The results of the research points to three main conclusions, first, history Preamble formulation loaded with manipulation of facts, especially related to the Pancasila. Second, the law scientifically, there are complications surrounding hirearki theoretical law and legal sources in assessing Preamble both its existence and its significance as a legal text. The complications associated with issues such as text meta-yuristik Declaration of Independence in 1945 and Pancasila. Third, the legal framework regarding the inventory of where lies Preamble as a source of law and within the law in Indonesia hirearki not get significant position, although its strength doctrinally and objective circumstances empirically demonstrated, that Preamble born a juridical act, in the nature of space consensus philosophical-juridical. Keywords: History, Power of Law, Legal Force, Comparative Legal Systems